Isoquercitrin alleviates pirarubicin-induced cardiotoxicity in vivo and in vitro by inhibiting apoptosis through Phlpp1/AKT/Bcl-2 signaling pathway - Wang, Lei; Ma, Jiulong; Chen, Chen; Lin, Bin; Xie, Sicong; Yang, Weiwei; Qian, Jiajia; Zhang, Yang (Frontiers in Pharmacology, 2024)
Due to the cardiotoxicity of pirarubicin (THP), it is necessary to investigate new compounds for the treatment of THP-induced cardiotoxicity. Isoquercitrin (IQC) is a natural flavonoid with anti-oxidant and anti-apoptosis properties. Thus, the present study aimed to investigate the influence of IQC on preventing the THP-induced cardiotoxicity in vivo and in vitro. Results showed that IQC reduced THP-induced myocardial histopathological injury, electrocardiogram (ECG) abnormalities, and cardiac dysfunction in vivo. IQC also decreased serum levels of MDA, BNP, CK-MB, c-TnT, and LDH, while increasing levels of SOD and GSH. We also found that IQC significantly reduced VDAC1, ANT1, and CYPD mRNA expression. In addition, IQC controlled apoptosis by modulating Phlpp1/AKT/Bcl-2 signaling pathways. IQC markedly increased H9c2 and HCM cell viability and SOD levels, diminished the levels of ROS and MDA, and elevated mitochondrial function in H9c2 and HCM cells to defend against THP-induced cardiomyocyte apoptosis in vitro. The AKT inhibitor IMQ demonstrated that IQC lacked antioxidant and anti-apoptotic properties. Moreover, our data showed that IQC regulates Phlpp1 expression, thereby influencing the expression levels of p-AKT, cytochrome c, caspase-3, caspase-9, Bcl-2, and Bax. In conclusion, our results indicate that IQC protects the changes in mitochondrial membrane permeability in cardiomyocytes by regulating the Phlpp1/AKT/Bcl-2 signaling pathway, inhibits the release of cytc from the mitochondrial inner membrane to the cytoplasm, forms apoptotic bodies, induces cell apoptosis, and reduces THP induced cardiotoxicity.